Fahr Syndrome Unknown Complication: Overactive Bladder - Devrim Tuglu; Ercan Yuvanç; Fatih Bal; Yakup Türkel; Ersel Dağ; Erdal Yılmaz; Ertan Batislam (Case Reports in Urology)
A 38-year-old male patient was admitted to our outpatient department because of frequency and urgency incontinence. During evaluation it was detected that the patient was suffering from frequency which was progressive for one year, feeling of incontinence, and urgency incontinence. There was no urologic pathology detected in patient’s medical and family history. Neurologic consultation was requested due to his history of boredom, reluctance to do business, balance disorders, and recession for about 3 years. Brain computerized tomography (CT) scan revealed that amorphous calcifications were detected in the bilaterally centrum semiovale, basal ganglia, capsula interna, thalami, mesencephalon, pons and bulbus, and the bilateral cerebellar hemispheres. We have detected spontaneous neurogenic detrusor overactivity without sphincter dyssynergia after evaluating the voiding diary, cystometry, and pressure flow study. We consider the detrusor overactivity which occurred one year after the start of the neurological symptoms as the suprapontine inhibition and damage in the axonal pathways in the Fahr syndrome.